A stepwise enumeration optimization method for large-scale seawater-source heat pump system with multiple beach wells. (August 2021) - Xin, Jia; Lin, Duanmu
Abstract: Beach wells are designed for pumping seawater in the seawater-source heat pump (SWHP) system with low-energy consumption. However, the multi-wells SWHP system is a complex system that has multi-objectives (energy consumption and lifetime cost) and multi-factors (land width and length, the arrangement of beach wells, permeability, and specific heat capacity of rock-soil). The system optimization assignment becomes a formidable work due to the increased number of beach wells with increasing energy system scale, and this paper aims to study the system optimization method to meet the energy-saving requirements of building engineering. A stepwise enumeration optimization method is developed for efficient optimization of the multi-wells SWHP system. Based on the established mathematical models, the numerical simulation method is used in the optimization procedure. A case study is conducted, the optimization parameters are obtained: 1260 J/(kg·°C) and 0.0007 m/s of physical parameters, 750 m width and 500 m length of land size, one row and three columns of beach wells, the research result indicates that a greater land size and a greater number of beach wells is not the optimal solution. The proposed stepwise enumeration method provides higher precision and better analyticity than the orthogonal method. Also, the optimization speed is improved compared to the enumeration method. Enumeration requires 5 6 calculation times, while the stepwise enumeration method needs only 100 calculation times. As such, the proposed method is feasible and effective in optimizing the multi-wells SWHP system, and the corresponding optimization results can scientifically guide system design. Highlights: A stepwise enumeration optimization methodology is proposed. Computing models of system optimization are given. Multi-objectives and multi-factors of a heat pump system are analyzed.